1974
DOI: 10.1901/jaba.1974.7-93
|View full text |Cite
|
Sign up to set email alerts
|

SOCIOMETRIC AND DISRUPTIVE BEHAVIOR AS A FUNCTION OF FOUR TYPES OF TOKEN REINFORCEMENT PROGRAMS1

Abstract: Children in a first-grade dassroom were divided into four groups. Baseline measures of disruptive classroom behavior were taken on a well-behaved and disruptive child in each group. Following baseline, four types of token economies were simultaneously introduced and rotated every 10 days within a Latin Square design. The token economies were: (1) individual reinforcement determined by individual performance; (2) group reinforcement determined by the behavior of the most disruptive child; (3) group reinforcemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 15 publications
2
44
0
Order By: Relevance
“…In this regard, behavior analysis could make a significant contribution. Drabman, Spitalnik, and Spitalnik (1974), for example, reported a study in which sociometric status was shown to be a function of a group tokenreinforcement system. The authors concluded that behavior-modification techniques could be employed to change sociometric status.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, behavior analysis could make a significant contribution. Drabman, Spitalnik, and Spitalnik (1974), for example, reported a study in which sociometric status was shown to be a function of a group tokenreinforcement system. The authors concluded that behavior-modification techniques could be employed to change sociometric status.…”
Section: Discussionmentioning
confidence: 99%
“…Token economies have frequently been implemented in the classroom to both increase appropriate behavior (Putnam, Handler, Ramirez-Platt & Luiselli, 2003;Herring & Wilder, 2006) and to decrease disruptive behavior (Drabman, Spitalnik, & Spitalnik, 1974;. The educational literature on classroom management now includes recommendations on how to implement token economies within the classroom for individual students Macciomei, 1999;Ward, 1991) and for the entire classroom (Axelrod, 1998;.…”
Section: Token Economiesmentioning
confidence: 99%
“…For example, tokens can be given and never removed (Drabman, Spitalnik, & Spitalnik, 1974;Kirby, Kerwin, Carpenedo, Rosenwasser, & Gardner, 2008;. The teacher may present a token each time a desired behavior occurs and never remove tokens when an undesired behavior occurs.…”
Section: Token Economiesmentioning
confidence: 99%
“…Occasionally, published reports have included client evaluations of treatment procedures by mentioning anecdotal information about how institutional staff, parents, and clients prefer one treatment technique over another (Drabman, Spitalnik, & Spitalnik, 1974;Foxx & Azrin, 1972. In some cases, questionnaire data have been obtained about staff or client satisfaction with treatment (Foxx & Shapiro, 1978;Liberman, Levine, Wheeler, Sanders, & Wallace, 1976;Porterfield, Herbert-Jackson, & Risley, 1976;Rosenbaum, O'Leary, & Jacob, 1975;Webster & Azrin, 1973).…”
Section: The Pennsylvania State Universitymentioning
confidence: 99%